2008
DOI: 10.3174/ajnr.a1026
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Intralabyrinthine Schwannomas: A Retrospective Study of 52 Cases with Emphasis on Lesion Growth

Abstract: BACKGROUND AND PURPOSE:Only a few case reports and small series of intralabyrinthine schwannomas (ILSs) have been reported. The purpose of this study was to assess prevalence, MR characteristics, location, clinical management, and growth potential/patterns of ILSs in the largest series reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
64
2
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 22 publications
1
64
2
9
Order By: Relevance
“…In other reported series, intracochlear and Tumor confined to the cochlea Transmodiolar (13) Tumor centered in the cochlea with extension through the modiolus into the IAC Intravestibular (7) Tumor centered in vestibule (Ϯ semicircular canal involvement) Transmacular (4) Tumor centered in the vestibule with extension into the IAC via the macula cribrosa Vestibulocochlear (5) Tumor within the vestibule and cochlea Transotic (2) Tumor within the labyrinth with extension into the IAC and middle ear transmodiolar tumors were reported in 88 cases; intravestibular and transmacular, in 40 cases; vestibulocochlear, in 5 cases; and transotic, in 4 cases. 1,23,29,30 A similar classification scheme was offered on many of the same patients. 1 An additional 17 cases were added to our original dataset since the initial presentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other reported series, intracochlear and Tumor confined to the cochlea Transmodiolar (13) Tumor centered in the cochlea with extension through the modiolus into the IAC Intravestibular (7) Tumor centered in vestibule (Ϯ semicircular canal involvement) Transmacular (4) Tumor centered in the vestibule with extension into the IAC via the macula cribrosa Vestibulocochlear (5) Tumor within the vestibule and cochlea Transotic (2) Tumor within the labyrinth with extension into the IAC and middle ear transmodiolar tumors were reported in 88 cases; intravestibular and transmacular, in 40 cases; vestibulocochlear, in 5 cases; and transotic, in 4 cases. 1,23,29,30 A similar classification scheme was offered on many of the same patients. 1 An additional 17 cases were added to our original dataset since the initial presentation.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,16,17,22,23,26 More advanced imaging and characterization with high-resolution T2 and gradient recalled-echo sequences appeared in the literature in the early 2000s. 1,21,[28][29][30][31] Some reports have suggested that the lesions can be invisible on T2 and even postgadolinium T1-weighted images. 10,17,26 This insensitivity may have been due to section thickness and less optimized imaging sequences at that time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,25,31 These outcomes may be partially due to lack of standardization of criteria for severity based on imaging findings 8,12,13 but also may reflect the spectrum of findings through the range associated with the natural history of Menière disease. The delayed post-IT injection FLAIR sequence should be interpreted with multiplanar projections, to avoid interpretation errors due to partial volume averaging as illustrated in Fig 2. Additionally, any nonstandard sequences must be reviewed in the context of a full IAC protocol, including fluid-sensitive, DWI, FLAIR, and postcontrast T1 sequences of the entire auditory pathway, to exclude a schwannoma 32 or other source of…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of intralabyrinthine schwannoma is still rare. To date, only about 140 cases have been reported [9,10], but due to the improvement of magnetic resonance imaging techniques the number of detected cases is rising. Depending on the location of the tumor, intralabyrinthine schwannomas can be differentiated into seven categories: Intravestibular, intracochlear, intravestibulocochlear, transmodiolar, transmacular, transotic and tympanolabyrinthine [11].…”
mentioning
confidence: 99%